Criminal aspects of battling corruption in state authorities (Journal of Universal Science Research, 2023)
This article covers the causes of corruption in state administration bodies, the reforms implemented in it, and actions aimed to prevent corruption.Also, in the process of socio-economic and political changes taking place in our country, the study and research of problems such as the danger of corruption and the need to fight against it, the fact that it is a dangerous socio-political phenomenon for the society, and the fact that the fight against corruption is the demand of the time, is a means that led to these reasons. analyzed.An attempt was made to determine the socio-economic grounds of the emergence of corruption and the reasons for its increase. The importance of the issues of corruption and the fight against them in the state management bodies was emphasized.